Extended adjuvant endocrine therapy – A standard to all or some?. (April 2017) - Ribnikar, Domen; Sousa, Berta; Cufer, Tanja; Cardoso, Fatima
Abstract: Patients with estrogen receptor-positive (ER +) early breast cancer (EBC) are at a continuous risk for distant relapse despite 5 years of standard endocrine therapy, even after 10–15 years after primary diagnosis. Hence, large randomized clinical trials were conducted to evaluate the role of extended endocrine treatment (ET) with the primary goal to prevent or at least delay distant relapse. Two very large trials of extended tamoxifen (TAM), the ATLAS and the aTTom trial, proved the efficacy of prolonged TAM particularly important after 10 years due to the carry-over effect of the five initial years. Additionally, the extended use of AIs after 5 years of tamoxifen, also proved to be efficacious in preventing late distant relapses. For letrozole (LET) it was shown in the MA.17 trial that it also improves overall survival (OS) in node-positive BC patients. There are many options and still unanswered questions related to extended ET, which are discussed in this review. The most important issue in deciding prolonged duration of ET is undoubtfully how to identify ER+ patients who benefit most from this approach. With this purpose, not only classical pathological factors have been studied, but also molecular profiles of individual tumors, which might help us in the near future to better tailor ET. Not only efficacy, but also toxicity of such prolonged treatment is essential for optimal use, particularly maintained compliance in a routine clinical practice. These issues are discussed in this review. Highlights: Most patients with ER+ EBC are at continuous risk of relapse after diagnosis despite of 5 years of adjuvant tamoxifen treatment. Tamoxifen and AIs have saved many lives, and their extended use provide yet further benefits, as shown in meta- analyses. Balancing toxicity versus efficacy of long-term ET is highly important. There are many unanswered questions such as the optimal duration of extended ET, the optimal sequencing of tamoxifen and AIs, whether intermittent ET is superior to continuous and especially, which patients are the best candidates for prolonged use of ET that will benefit most with minimal toxicity. Improved knowledge of molecular biology of endocrine responsive EBC may in near future certainly help to better tailor ET for the individual patient.